Postcolonial ecocriticism and the notion of invisibility in four francophone novels from West Africa - Akanji, Waidi Adewale (My University, 2020)
This study aims at contributing to postcolonial ecocriticism as well as African literary criticism by examining imagery of ecology in four postcolonial francophone African novels from Senegal, Guinea, and Côte d’Ivoire. Despite the fact that Africa is conceived as a colonial ecological imaginary as can be seen in names of countries such as Ivory Coast, Gold Coast etc., there are few studies on environmentalism in the literature of this region. Except for the Anglophone area, studies on environmentalism havenot been given adequate attention in the francophone African literature of this region. This study seeks to fill this gap by proposing the notion of invisibility as sociopolitical, economic forces, and actions or activities whose causes seem to be immediately “invisibles” but over time have harmful or disastrous effects on the ecology in West Africa in order to underscore ecological discourse in the francophone literature of this region. Our analysis of invisibility is based on postcolonial ecocriticism as a transdisciplinary theoretical framework, especiallyconcepts of“Slow Violence” (Rob Nixon) and “Anthropocene” (Timothy Clark) that raise the question of temporality in ecological discourse. In this study, we use geocriticism as a tool to examine literary representation of humans’ relationship with geographical spaces of postcolonial African nations. According to the conception of ecology in this study, the choice of novels focuses on humans’ relations with the environment during the postcolonial period. The first part of the study will be devoted to an analysis of slow violence in urban environment context and sociopolitical forces in Aminata Sow Fall’s La grève des Bàttu(Senegal 1979)and Tierno Monénembo’s Les écailles du ciel (Guinea 1986). The second part will be a comparative analysis of political and economic forces that lead to the looting of natural resources in context of war in Ahmadou Kourouma’s Allah n’est pas obligé(2000) and Quand on refuse on dit non(2004). In this study, we observe that the interaction between visible effects and causes(economic, political and ideological) which are often invisible of environmental degradation are taking into account when discussing the evolution of this interaction in francophone African literature from independence till neocolonialism (especially Francafrique). It leads us to a re-conceptualisation of an ecological discourse, as well as the notion of anthropocene in francophone African literature
A thesis submitted in fulfilment of the requirements of the degree of Doctor of Philosophy (PhD), School of Literature, Language and Media, University of the Witwatersrand, 2020